THE USE OF THE ABOGE CALENDAR IN THE JAMBI MANUSCRIPTS: Power and Cultural Relations between Sultanates (JOURNAL OF INDONESIAN ISLAM, 2024)
This article aims to describe the use of the Aboge calendar system in Jambi Sultanate manuscripts and analyze the historical context of the period. The research used the philological method to elaborate the manuscripts and then applied historical and astronomical approaches to study the texts. The study involved some 17th to 20th-century manuscripts of the Sultanate of Jambi that use colophons in the Aboge calendar style. Although some of the Aboge calendars in the manuscripts cannot be converted into the Hijri and Christian calendars, the analysis of the Aboge calendar in these manuscripts strengthens the argument related to the influence of Javanese Kingdom of Mataram on the Jambi Sultanate, as known in Jambi Sultanate history, both power and cultural relations. In contrast, the use of the Aboge calendar in Jambi also shows the relationship between the Jambi Sultanate with Aceh and West Sumatra, where some of the Aboge reflect Aceh and Tariqa Shattariya modifications.